Eswl for Upper Ureteric Stone With and Without JJ Stent-A Comparative Study - singh, Promode Ranjan; alim, Md Abdul; islam, Md Shafiqul; ahmed, Kaiser; choudhury, Jalal Ahmed (Bangladesh Journal of Urology, 2020)
Objective: To find out the outcome of stenting before ESWL in the management of upper ureteric stone. Methods and materials: This prospective comparative study was conducted in the department of urology, Sylhet Osmani Medical College Hospital from January 2011 to June 2012. Sixty two patients with upper ureteric stone, aged between 18 to 60 years irrespective of sex, unilateral radio opaque upper ureteric stone of greatest diameter 2cm, patients with normal renal function and negative urine culture and were agreed to participate in the study were selected. Selected 62 patients with upper ureteric stones were divided randomly into group-A and group-B each consisting 31 patients. The patients of group-A were treated with ESWL with a JJ stent and that of group-B without JJ stent. In the patients selected for JJ placement, a 5 fr JJ stent was placed under regional anaesthesia before ESWL. Siemens Lithotripsy ESWL machine was used to impart shock waves and 3500 shockwaves was given in a session. Both the groups were compared for stone clearance, ureteric colic, steinstrasse, fever, lower urinary tract symptoms (LUTS), number of ESWL sessions. Data were processed and analyzed using software SPSS. Results: The number ESWL session in stented group [single session 10 (32.3%) and multiple sessions 21 (67.7%)] and in non-stented group [single session 9 (29.0%) and multiple sessions 22 (71.0%)] was similar in both groups (p>0.05) Stones were cleared in 23 (74.2%) patients in stented group and 25 (80.6%) patients in non-stented group. Difference was not statistically significant (p>0.05). Ureteric colic was significantly fewer in stented group than that of non-stented group [4 (12.9%) vs 11 (35.5%); p<0.05] but surapubic pain was significantly more in stented group than that of non-stented group [13 (41.9%) vs 5 (16.1%); p<0.05]; while steinstrasse [3 (9.7%) vs 5 (16.1%); p>0.05] and fever [5 (16.1%) vs 2 (6.5%); p>0.05] did not differ statistically significant between groups. Lower urinary tract symptoms such as urinary frequency [15 (48.4%) vs 3 (9.7%); p<0.01]; urgency [17 (54.8%) vs 5 (16.1%); p<0.01] and dysuria [19 (61.3%) vs 6 (19.4%); p<0.01] were significantly more in stented group than that of non-stented group; but gross haematuria [21 (67.7%) vs 15 (48.4%); p>0.05] were more in stented group. Conclusion: ESWL is an effective and reasonable initial therapy in the management of upper ureteric stones measuring <2 cm. Pre-ESWL ureteric stenting provides no additional benefit over non-stented ESWL in their management. Moreover, stents are associated with signiûcant patient discomfort and morbidity. Bangladesh Journal of Urology, Vol. 17, No. 1, Jan 2014 p.17-22